Molecular Modeling and Simulation: An Interdisciplinary Guide An Interdisciplinary Guide - Schlick, Tamar; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2010)
Review of previous edition: (3z(BI am often asked by physicists, mathematicians and engineers to recommend a book that would be useful to get them started in computational molecular biology. I am also often approached by my colleagues in computational biology to recommend a solid textbook for a graduate course in the area. Tamar Schlick has written the book that I will be recommending to both groups. Tamar has done an amazing job in writing a book that is both suitably accessible for beginners, and suitably rigorous for experts.(3y (BJ. J. Collins, Boston University, USA. (3z(BMolecular modeling $1! = (Bis now an important branch of modern biochemistry. $1! = (BSchlick has brought her unique interdisciplinary expertise to the subject. $1! = (BOne of the most distinguished characteristics of the book is that it makes the reading really fun $1! = (Band the material accessible. $1! = (Ba crystal clear logical presentation $1! = (B. Schlick has added a unique title to the collection of mathematical biology textbooks $1! = (B. a valuable introduction to the field of computational molecular modeling. It is a unique textbook $1! = (B.(3y (BHong Qian, SIAM Review, 2005.s
Biomolecular Structure and Modeling: Historical Perspective -- Biomolecular Structure and Modeling: Problem and Application Perspective -- Protein Structure Introduction -- Protein Structure Hierarchy -- Nucleic Acids Structure Minitutorial -- Topics in Nucleic Acids Structure: DNA Interactions and Folding -- Topics in Nucleic Acids Structure: Noncanonical Helices and RNA Structure -- Theoretical and Computational Approaches to Biomolecular Structure -- Force Fields -- Nonbonded Computations -- Multivariate Minimization in Computational Chemistry -- Monte Carlo Techniques -- Molecular Dynamics: Basics -- Molecular Dynamics: Further Topics -- Similarity and Diversity in Chemical Design.
Keywords: Mathematics; Biochemical engineering; Computer simulation; Biochemistry; Mathematics; Mathematical and Computational Biology; Biochemical Engineering; Simulation and Modeling; Biochemistry, general; Biophysics and Biological Physics